Recognition of Facial Emotional Expressions Among Italian Pre-adolescents, and Their Affective Reactions - Mancini, Giacomo; Biolcati, Roberta; Agnoli, Sergio; Andrei, Federica; Trombini, Elena (Frontiers in Psychology, 2018)
The recognition of emotional facial expressions is a central aspect for an effective interpersonal communication. This study aims to investigate whether changes occur in emotion recognition ability and in the affective reactions (self-assessed by participants through valence and arousal ratings) associated with the viewing of basic facial expressions during preadolescence (n = 396, 206 girls, aged 11–14 years, Mage = 12.73, DS = .91). Our results confirmed that happiness is the best recognised emotion during preadolescence. However, a significant decrease in recognition accuracy across age emerged for fear expressions. Moreover, participants’ affective reactions elicited by the vision of happy facial expressions resulted to be the most pleasant and arousing compared to the other emotional expressions. On the contrary, the viewing of sadness was associated with the most negative affective reactions. Our results also revealed a developmental change in participants’ affective reactions to the stimuli. Implications are discussed by taking into account the role of emotion recognition as one of the main factors involved in emotional development.